Выбор цифровой камеры для оптического микроскопа - Borovitsky, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A method is considered for the proper selection of a digital camera for an optical microscope, taking into account their spatial resolution. Four types of digital cameras are examined as image sensors for optical microscopes: a color camera with a Bayer filter, a full-color camera, a color camera with a Bayer filter and microscanning, and a full-color camera with microscanning. Recommendations are presented for the correct choice of these digital cameras.